Propriedades semânticas e pragmáticas de modificadores do núcleo do sintagma nominal - Nhoato, Helker [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
O objetivo do trabalho é analisar funcionalmente os modificadores adjetivais do SN com base na motivação semântica do referente nuclear: se entidades de primeira ordem ou Indivíduos ou se entidades de segunda ordem ou Estados de Coisas (LYONS, 1977; HENGEVELD, 2008), priorizando as propriedades pragmáticas e semânticas dos adjetivos na variedade do português brasileiro falado no noroeste do Estado de São Paulo. A análise, de natureza funcionalista, vincula-se ao arcabouço teórico proposto pela Teoria da Gramática Funcional (DIK, 1997a) e pela Gramática Discursivo-Funcional (HENGEVELD; MACKENZIE, 2008) que proveem uma classificação semântica dos constituintes do sintagma nominal com base nas suas propriedades de referência a entidades do mundo e na atribuição de propriedade de modificação a essas entidades. Para análise da relação que os modificadores estabelecem com o núcleo dos sintagmas nominais, este trabalho volta-se para a classificação proposta por Negrão et al. (2014), que separam os adjetivos em argumentais e predicadores de núcleo, ou seja, itens lexicais que assumem uma posição aberta pelo substantivo deverbal e os que abrem posições temáticas que são, por seu lado, saturadas por um substantivo-núcleo. Para análise dos aspectos semânticos dos modificadores utilizam-se as classificações propostas por Castilho (2010), Castilho e Moraes de Castilho (1993), Cinque (2010) e Neves (2010). A amostra examinada é extraída do córpus IBORUNA coletado pelo Projeto ALIP, que foi concebido no interior do Grupo de Pesquisa em Gramática Funcional (GPGF) da UNESP de São José do Rio Preto. Os dados mostram, em primeiro lugar, que, de certo modo, independentemente do tipo de entidade envolvido no núcleo, de primeira e de segunda ordem, a posição pós-nuclear é a preferência grandemente majoritária dos adjetivos na codificação morfossintática. Além disso, a distribuição em anteposição e posposição tem uma regularidade motivada por traços semânticos específicos do modificador. A posição pré-nuclear, mesmo com baixa frequência, está vinculada a traços pragmáticos e semânticos específicos. Esses resultados demonstraram a atuação de motivações semânticas e, em menor parte, pragmáticas, condicionando o preenchimento de posições específicas dos modificadores no interior do sintagma nominal.

The aim of this study is to analyze, from a functional perspective, the adjectival modifiers of Noun Phrases, focusing on the semantic motivation of the Noun Phrase head: whether headed by first-order entities or Individuals or second-order entities or States-of-Affairs (LYONS, 1977; HENGEVELD, 2008). The purpose of this work is to give some priority to the pragmatic and semantic properties of adjectival modifiers in the variety of Brazilian Portuguese spoken in the northwest of São Paulo State. In order to do so, the analysis based on a functional perspective is aligned to the theoretical framework of The Theory of Functional Grammar (DIK, 1997a) and of the Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008). These authors provide a semantic classification of the constituents of the Noun Phrases which is based on their reference to entities (Individuals or States-of-Affairs) of a world and they analyze the process of modification of these entities by the attribution of a property. The analysis of the relationship between modifiers and the head of the Noun Phrases, initially, considers the classification proposed by Negrão et al. (2014), who distinguish adjectives in arguments and predicates. This distinction means that lexical items that, on the one hand, take a position open by the deverbal noun and, on the other hand, those who open a thematic positions taken by the nuclear referent of the Noun Phrase. Moreover, to analyze the semantic aspects of the modifiers, this study considers the classifications proposed by Castilho (2010), Castilho and Moraes de Castilho (1993), Cinque (2010) and Neves (2010). The sample examined was extracted from the IBORUNA Corpus, which was conceived by the Functional Grammar Research Group (Grupo de Pesquisa em Gramática Funcional), of São Paulo State University (UNESP) at São José do Rio Preto. The analysis shows, firstly, that: regardless of the type of entity involved in the head, whether first or second order, the modification after the head (postmodification) is where the adjective is largely preferred to occur in Morphosyntactic Encoding. In addition, the distribution through the place before the head (premodification) and postmodification in relation to the Noun Phrase head is provided with a high degree of regularity motivated by specific semantic features of the modifier. Secondly, the premodification, even if it is applied with low frequency in the data, is properly aligned to pragmatic and semantic specific features. Finally, these results show how semantic motivations and, less frequently, pragmatic ones, are involved in the fulfilling of specific positions of adjectives inside the Noun Phrase.
Semantic and pragmatic properties of modifiers of the noun phrase head
Keywords: Funcionalismo; Modificador; Adjetivo; Sintagma Nominal; Semântica; Pragmática; Functionalism; Modifier; Adjective; Noun Phrase; Semantics; Pragmatics